DEKONSTRUKSI PADA CERPEN SERIBU KUNANG-KUNANG DI MANHATTAN KARYA UMAR KAYAM - Djaha, Siti Susanti Mallida (MIMESIS, 2021)
This study aims at analyzing the deconstruction process in the short story Seribu Kunang-Kunang di Manhattanby Umar Kayam by looking at the binary oppositions as well as the form of deconstruction that happens in the short story. The theory used in this study is deconstruction theory by Jacques Derrida. The result showed that there were several binary oppositions, namely: West and East, big city and village, man and woman. The oppositions described in this story are problematic. The first opposition, West and East, was reversed and won by the East. The second opposition, the city and the village, experienced a reversal so that the village won. Likewise, with the third opposition, man and woman also experienced a reversal and won by the woman. In the end, this research shows that these hierarchical oppositions do not exist and are only the result of the construction of the author's imagination. Yet the author rejects what he wants to portray in the story, the Western life in Manhattan, United States.